PREVALENCE AND FACTORS ASSOCIATED WITH STIGMA AMONG PSYCHIATRIC PATIENTS AGED BETWEEN 20 AND 80 YEARS AT NEUROPSYCHIATRIC HOSPITAL, CARAES NDERA, RWANDA - Emile Hatangimana, Dr. Rosemary Okova (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: Public stigma related to mental health illnesses (PSRMHIs) remain a major public health threat globally including in Rwanda where about 20% of its population has at least one mental health issue and at risk of PSRMHIs. Aim: This research aimed to determine the prevalence and factors associated with mental health stigma among psychiatric patients. Setting: Neuropsychiatric Hospital, Caraes Ndera, Rwanda Methods: This study was a quantitative cross-sectional study. Results: Of the 419 psychiatric patients aged between 20 to 8 years with mean age 32, 71.8 % experienced PSRMHIs. Factors associated with stigma, increase in socio-cultural norms, number of government policies, loss of schooling, and loss of spouse or relative, and poverty there is significant positive predictive increase of the log odds 4.549 at p-value of significance level of 0.001 there is a predictive likelihood of strengthening stigma with significant positive predictive causal relationship. This study found non-significant causal relationship between socio-demographic factors and stigma, suggesting that for every one unity increase in those factors, there is a decreased probability of experiencing higher level of stigma, with log odds of -0.011 at p-value of 0.976. Conclusion: This study shows that PSRMHIs remain high among psychiatric patients, and it increases by lack of life opportunities and due to lack of community awareness on anti-discriminatory behaviors. Contribution: The significance is to inform the government and mental health partners on the burden of stigma to revise and develop new mental health promotion programs.